Carreadores lipídicos nanoestruturados contendo doxorrubicina, ácido docosahexaenóico e succinato de α-tocoferol: formulação, caracterização e avaliação do potencial terapêutico contra o câncer. - Eduardo Burgarelli Lages (2021)
Encapsulation of doxorubicin (DOX) in nanocarriers has been proposed to overcome its limitations. In this work, a nanostructured lipid carriers (NLC) formulation containing DOX and the anticancer adjuvants docosahexaenoic acid (DHA) and αtocopherol succinate (TS) was developed. NLC was prepared by the emulsificationultrasound method and DOX was later incorporated, which prevented its degradation during manufacturing. High DOX encapsulation efficiency was obtained due to the formation of an ion pair with TS, which decreased its aqueous solubility and reduced its crystallinity. In vitro studies indicated that the combination of DOX, DHA and TS has synergistic effects against 4T1 tumor cells. The formulation showed high antitumor efficacy by reducing 4T1 tumor growth in mice, in addition to decreasing DOX-induced systemic toxicity. Despite these promising results, the evaluation of pharmacokinetics after intravenous administration in mice revealed a similar pharmacokinetic profile between the nanocarrier and free DOX (solution), suggesting rapid destabilization of the ion pair and release of DOX. From these data, the synthesis of DOX-TS covalent conjugates was proposed to increase the retention of DOX in NLC. DOX was successfully conjugated to TS via an amide or hydrazone bond. In vitro studies indicated high cytotoxicity of the hydrazone derivative against 4T1 cells, unlike the amide conjugate. The encapsulation of the hydrazone derivative in the NLC system, plus DHA, resulted in reduced particle size (90 nm), high encapsulation efficiency, and pH-sensitive DOX release. This formulation showed a better pharmacokinetic profile compared to free DOX and the previously prepared formulation (ion pair). In vivo studies revealed great therapeutic potential for this nanocarrier, which was able to prevent the development of acute cardiotoxicity in mice, considerably inhibit the 4T1 tumor growth and reduce the systemic toxic effects caused by DOX. These results indicate that the NLC system containing DHA and the hydrazone DOX-TS conjugate may be a promising formulation for cancer treatment.